Structural and functional coupling alterations in autism spectrum disorder with and without comorbid attention deficit hyperactivity disorder - Zhang, Xiaolin; Zhou, Yan; Hu, Luming; Yan, Jingwen; Yin, Xuntao (Frontiers in Psychiatry, 2026)
BackgroundAutism spectrum disorder (ASD) and attention deficit hyperactivity disorder (ADHD) are highly comorbid. The neural basis of this comorbidity remains unclear. We compared brain structural-functional coupling (SC-FC coupling) across ASD subgroups and typically developing (TD) controls to parse the neurobiological heterogeneity of ASD.MethodsWe analyzed T1-weighted and resting-state fMRI data from 331 participants from ABIDE II (130 ASD [39 ASD+ADHD, 91 ASD-only] and 201 TD). For each participant, we extracted multivariate structural features from T1-weighted images to construct an individual structural covariance network. SC-FC coupling for each brain region was quantified by correlating its observed functional connectivity profile with the profile predicted from individual structural features via linear regression.ResultsCompared to TD individuals, the ASD group showed altered SC-FC coupling in networks critical for social cognition, emotion, sensory processing, and cognitive control: the default mode network (DMN), limbic system (LimN), somatomotor network (SMN), and frontoparietal network (FPN). Crucially, distinct patterns emerged between ASD subgroups. The ASD-only group had stronger coupling in the left inferior temporal gyrus (ITG.L). The ASD+ADHD group showed increased coupling in specific cerebellar regions: the right cerebellar lobule IX (Cerebellum_9_R) and right cerebellum Crus II (Cerebellum_Crus2_R).ConclusionsOur findings demonstrate both shared and subtype-specific alterations in SC-FC coupling in ASD. Comparing ASD subgroups clarifies that comorbid ADHD is associated with unique neural pathways, particularly involving cerebellar integration for attentional processes. Measuring SC-FC coupling offers a valuable approach for disentangling the heterogeneity in ASD and may aid in developing targeted interventions.